2017
DOI: 10.1038/s41598-017-00943-w
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa cell endothelin-2 expression is fundamental for ovulatory follicle rupture

Abstract: Ovulation is dependent upon numerous factors mediating follicular growth, vascularization, and ultimately oocyte release via follicle rupture. Endothelin-2 (EDN2) is a potent vasoconstrictor that is transiently produced prior to follicle rupture by granulosa cells of periovulatory follicles and induces ovarian contraction. To determine the role of Edn2 expression, surgical transplant and novel conditional knockout mice were super-ovulated and analyzed. Conditional knockout mice utilized a new iCre driven by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…Interestingly, the present results showed that expressions and activation of NLRP3 inflammasomes in the outside of intrafollicular fluid after PMSG-52 h treatment, suggesting the regional responses in the ovulatory follicles (Duffy et al, 2019), which contributed to the apical stretching and thinning (Duffy et al, 2019). Previous studies have indicated ETs facilitated follicular rupture at the apex (Ko et al, 2006; Choi et al, 2011; Cacioppo et al, 2017) and HIF-1α regulated ovulation-related gene expression (Zhang Z. et al, 2011; Wang et al, 2012; Wang et al, 2015) during the ovulatory process. Therefore, the present study further examined the expressions of HIF-1α and ET-1 and found their expression patterns were similar with NLRP inflammasomes, demonstrating the possible contribution of NLRP inflammasomes to the ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the present results showed that expressions and activation of NLRP3 inflammasomes in the outside of intrafollicular fluid after PMSG-52 h treatment, suggesting the regional responses in the ovulatory follicles (Duffy et al, 2019), which contributed to the apical stretching and thinning (Duffy et al, 2019). Previous studies have indicated ETs facilitated follicular rupture at the apex (Ko et al, 2006; Choi et al, 2011; Cacioppo et al, 2017) and HIF-1α regulated ovulation-related gene expression (Zhang Z. et al, 2011; Wang et al, 2012; Wang et al, 2015) during the ovulatory process. Therefore, the present study further examined the expressions of HIF-1α and ET-1 and found their expression patterns were similar with NLRP inflammasomes, demonstrating the possible contribution of NLRP inflammasomes to the ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the 14 SIGLEC genes that exist are also expressed in villous and extravillous cytotrophoblasts, decidual cells, as early as eight gestational weeks, and in maternal uterine glands ( 39 , 40 ), suggesting a possible role of SIGLECs in mediating the immune tolerance at the feto-maternal interface. The EDN2 gene (1p34.2 locus) is associated with almost 5% lower time-to-spontaneous onset of delivery ( P -value= 2.3 × 10 −6 ), EDN2 encodes endothelin 2, a strong vasoconstrictor involved in follicular rupture and ovulation; it causes the contraction of the smooth muscle layer surrounding each follicle ( 41 , 42 ).…”
Section: Resultsmentioning
confidence: 99%
“…LOX encodes a member of the lysyl oxidase family proteins, which has previously been proposed to promote epithelial to mesenchymal transition in prostate cancer (Gonzalez-Chavarria et al, 2018), and its propeptide domain may display tumor suppressor activities (Agra et al, 2013). EDN2 belongs to the endothelin protein family of secretory vasoconstrictive peptides, and it has already been shown that it is involved in ovulation (Cacioppo et al, 2017). FOLR1 is a member of the folate receptor family, and a previous study showed it is associated with the progression of cervical cancer through the ERK signaling pathway (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%